Limb lengthening and peripheral nerve function—factors associated with deterioration of conduction - Simpson, A Hamish R W (Informa Healthcare, 2013)
BACKGROUND AND PURPOSE: Limb lengthening is performed for a diverse range of orthopedic problems. A high rate of complications has been reported in these patients, which include motor and sensory loss as a result of nerve damage. We investigated the effect of limb lengthening on peripheral nerve function. PATIENTS AND METHODS: 36 patients underwent electrophysiological testing at 3 points: (1) preoperatively, (2) after application of external fixator/corticotomy but before lengthening, and (3) after lengthening. The limb-length discrepancy was due to a congenital etiology (n = 19), a growth disturbance (n = 9), or a traumatic etiology (n = 8). RESULTS: 2 of the traumatic etiology patients had significant changes evident on electrophysiological testing preoperatively. They both deteriorated further with lengthening. 7 of the 21 patients studied showed deterioration in nerve function after lengthening, but not postoperatively, indicating that this was due to the lengthening process and not to the surgical procedure. All of these patients had a congenital etiology for their leg-length discrepancy. INTERPRETATION: As detailed electrophysiological tests were carried out before surgery, after surgery but before lengthening, and finally after completion of lengthening, it was possible to distinguish between the effects of the operation and the effects of lengthening on nerve function. The results indicate that the etiology, site (femur or tibia), and nerve (common peroneal or tibial) had a bearing on the risk of nerve injury and that these factors had a far greater effect than the total amount of lengthening.